Gaseous Emissions of a Combined Cogeneration Unit - Emil Toporcer; Vladimir Hlavna; A. Kovalcik (Communications - Scientific letters of the University of Zilina, 2009)
Problem of harmful gaseous emissions is solved in the paper in two ways. Firstly it is the design of amathematical model of flow and combustion in a combustion chamber of an engine, which is a component of a combined cogeneration unit with a proposal of solutions enabling the decrease in amount of harmful gaseous emissions. Secondly it is the verification of the solutions through the computation by means of mathematical models considering these solutions.